Kaizen implementation and its challenges in small and medium manufacturing firms: A case of Woliso Town, Ethiopia - Solomon Terfasa Dinka (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
In the modern world, industrial transformation receives great attention. As a result, many companies are becoming successful by implementing Kaizen as a change agent. Nevertheless, there were few pathways of continuous improvements, mainly because of abandonment of Kaizen philosophy, organizational resistance to change, lack of proper implementation and monitoring techniques, lack of employees’ motivation, and scarcity of resources. The study aimed to examine Kaizen implementation and its challenges in small and medium manufacturing firms of Woliso town. The study employed descriptive research adopting a quantitative research approach—the researcher used 55 small and medium manufacturing firms of Woliso town. In addition, the study employed primary data collected through open-ended and close-ended questionnaires. The study found that most sampled firms lack awareness about Kaizen because of a lack of training opportunities. Similarly, Kaizen philosophy is considered exhaustive and routine the attitude of owners, managers, and employees in Kaizen implementation is very weak. Finally, the study recommended that it is important to provide continuous training programs for employees and managers of small and medium manufacturing firms. Most importantly, to extend Kaizen's philosophy, it is essential to incorporate it into the school curriculum.